2017
DOI: 10.1038/s41598-017-14557-9
|View full text |Cite
|
Sign up to set email alerts
|

AQP3 is regulated by PPARγ and JNK in hepatic stellate cells carrying PNPLA3 I148M

Abstract: Aquaglyceroporins (AQPs) allow the movement of glycerol that is required for triglyceride formation in hepatic stellate cells (HSC), as key cellular source of fibrogenesis in the liver. The genetic polymorphism I148M of the patatin-like phospholipase domain-containing 3 (PNPLA3) is associated with hepatic steatosis and its progression to steatohepatitis (NASH), fibrosis and cancer. We aimed to explore the role of AQP3 for HSC activation and unveil its potential interactions with PNPLA3. HSC were isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Nuclei were counterstained with DAPI (Sigma‐Aldrich) and mounted (VECTASHIELD® Mounting Medium, Vector Laboratories) for microscope analysis (Olympus BX51). Relative quantification of IF staining was performed using Image J software in an automated fashion as seen previously . Channels were splitted for the respective fluorochrome (Red for PNPLA3 and Green for α‐SMA), and total fluorescence was quantified using macros in parallel for all the pictures taken.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclei were counterstained with DAPI (Sigma‐Aldrich) and mounted (VECTASHIELD® Mounting Medium, Vector Laboratories) for microscope analysis (Olympus BX51). Relative quantification of IF staining was performed using Image J software in an automated fashion as seen previously . Channels were splitted for the respective fluorochrome (Red for PNPLA3 and Green for α‐SMA), and total fluorescence was quantified using macros in parallel for all the pictures taken.…”
Section: Methodsmentioning
confidence: 99%
“…After AQP3 was silenced, the expression of the classic adipogenic factor PPARγ was significantly inhibited. PPARγ is an indispensable transcription factor for adipocyte differentiation [34], and a previous study has shown that AQP3 is the target of PPARγ in murine adipose cell line [35] and hepatic stellate cells [36]. The level of phosphorylation of AKT was also decreased, which indicates that the downstream signal of the classic insulin signaling pathway is weakened.…”
Section: Discussionmentioning
confidence: 92%
“…For immunofluorescence, slides were incubated with a cluster of differentiation 11b (CD11b) peridinin chlorophyll protein, cyanine 5.5–labeled antimouse (Mac‐1α chain, M1/70) (BD Biosciences) and counterstained with 4′,6‐diamidino‐2‐phenylindole (Sigma). Relative quantification of immunofluorescent staining was performed using Image J software in an automated fashion …”
Section: Methodsmentioning
confidence: 99%